1976
DOI: 10.3758/bf03199409
|View full text |Cite
|
Sign up to set email alerts
|

The effect of marker variability on the discrimination of temporal intervals

Abstract: This research investigates the human observer's ability to discriminate between the durations of two silent intervals, each interval preceded and followed by noise bursts called markers.The markers are separated· by T or T +~T' msec and T ranges from 0.3 to 1,000 msec.T is defined as that value of~T' for which the probability of discriminating T from T + AT' is 0.75. We compared the value of AT for conditions in which the markers were fixed in amplitude and duration with conditions in which the marker amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
50
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 5 publications
9
50
0
Order By: Relevance
“…Timbre judgments are typically made more quickly when participants respond to high-frequency tones with a key located high condition would be due to pitch uncertainty. This is in line with several studies showing that temporal judgments are affected by randomizing marker parameters (Grondin & Rousseau, 1991;Penner, 1976).…”
Section: Discussionsupporting
confidence: 76%
“…Timbre judgments are typically made more quickly when participants respond to high-frequency tones with a key located high condition would be due to pitch uncertainty. This is in line with several studies showing that temporal judgments are affected by randomizing marker parameters (Grondin & Rousseau, 1991;Penner, 1976).…”
Section: Discussionsupporting
confidence: 76%
“…However, we could not relate the results directly to rhythm perception and human auditory communication, for the following reasons. Most of the studies utilizing single time intervals had focused mainly on discrimination paradigms, and not on the subjective duration itself (Divenyi & Sachs, 1978;Grondin et al, 2005;Penner, 1976;Rammsayer & Leutner, 1996). This was in contrast with the fact that the studies utilizing multiple time intervals had often taken up subjective duration directly, with a clear interest in rhythm in music (e.g., Hasuo et al, 2011;Repp & Marcus, 2010;Schubert & Fabian, 2001;Yamashita & Nakajima, 1999).…”
mentioning
confidence: 73%
“…Previous research tested how the durations of events (i.e., sound markers) influenced the perception of time intervals in between events, either by utilizing single time intervals marked by two events (Divenyi & Sachs, 1978;Grondin, Ivry, Franz, Perreault, & Metthe, 1996;Grondin, Roussel, Gamache, Roy, & Ouellet, 2005;Penner, 1976;Rammsayer & Leutner, 1996;Woodrow, 1928) or by utilizing multiple time intervals marked by three or more events (Handel, 1993;Hasuo, Nakajima, & Hirose, 2011;Repp & Marcus, 2010;Schubert & Fabian, 2001;Yamashita & Nakajima, 1999). The results of these studies showed that marker duration could influence the perception of time intervals.…”
mentioning
confidence: 99%
“…541 There seems to exist a general agreement on the fact that when an observer is asked to discriminate between intervals of short duration, his performance is little affected by such stimulus characteristics as intensity, frequency, and bandwidth (Allan, 1979). More specifically, if the discrimination is performed on empty intervals marked by short auditory pulses, numerous studies have shown that, for intervals longer than 100 msec, performance is not sensitive to variations in marker intensity (Abel, 1972;Carbotte & Kristofferson, 1973;Divenyi& Danner, 1977;Penner, 1976), frequency or spectrum (Divenyi & Danner, 1977;Divenyi & Sachs, 1978), and duration (Abel, 1972;Carbotte & Kristofferson, 1973;Penner, 1976). Moreover, within the range of 0-100 msec, Nilsson (1969) and Oostenbrug, Horst, and Kniper (1978) have shown the performance to be relatively insensitive to changes in the energy of light pulse markers.…”
mentioning
confidence: 99%